Diversity of the insects in the diet of edible nest swiftlets in oil palm plantations - Syed Ab Rahman, Sharifah Farhana; Mohd Noor, Hafidzi; Burhanuddin, Maisarah (International Network for Natural Sciences, 2016)
The Edible Nest Swiftlet (Aerodramus fuciphagus) is a small bird from the family Apodidae which is commonly found in the South-East Asian region which characteristically roost and nest in cave or cavern-like situation. Swiftlet farming in specially designed building has recently developed due to high consumer demand for the edible bird nest. The farms are not the natural habitat of the swiflets and there are greater chance that this will affect in one way or the other way of their dietary habit and composition. The focus of this study was to investigate the diversity of insects found in the diet of A. fuciphagus in their habitats in oil palm-growing areas in Malaysia. This was achieved by investigating the relationship between insect composition in oil palm and insect prey composition in the feeding bolus of A. fuciphagus. The most common insects order found in the sampled fields of the three states in the study was Diptera (26.53%) and followed closely by Hymenoptera (21.26%). The difference between the sample sites as far as insects order composition is not significantly different (t test = 3.759 and 2.9). We failed to accept the H0 that the diversity of insect in the fields and diet of the swiftlets in all locations was the same.